Usos e potenciais das metodologias ativas em EPS pelas equipes de saúde: estudo de caso - Lemos, Felipe Magalhães (Universidade Federal de São Carlos, 2018)
The objective of this study was to analyze how the process of Permanent Health Education in the DRS XIV region occurs. As a SUS policy, the Permanent Health Education became a powerful tool for the implementation of Primary Health Care. The research was based on the principles of qualitative research and used interviews with health secretaries and participant observation in meetings of PHE, as a source of data collection. For the interpretation of the data, the technique of content analysis was applied. Two themes were found: (i) What is or is not permanent education; (ii) About the valuation of PHE. In the first theme, the sub-themes "Knowledge as a focus of practice" and "Modus operandi" show that 85% of secretaries and 100% of Health Unit workers understand Permanent Health Education as Continued Education and that 45% of secretaries expect proposed by DRS XIV. In the sub-theme on the valuation of the PHE it was noticed that there is some valuation on the part of some secretaries, but that in general this valuation does not occur, sometimes by economic impossibilities. Only two secretaries showed knowledge about Active Learning, and the practices observed were not guided by these methods. It was observed that there is evolution in the process of implementation of the Permanent Health Education practices, although most of the secretaries have only changed the name of the practices and maintained the actions of Continued Education. This work presents results that can help to change PHE practices through the use of Active Learning, helping to strengthen the work environments and guarantee the rights of SUS users.
Keywords: Educação Permanente em Saúde; Metodologias Ativas; Atenção Primária; Permanent Education in Health; Continued education; Active Learning; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA